Wax Myrtle Biology and Control in Pastures - Brent Sellers; Jason Ferrell; Reyna Speckmann (EDIS)
SS-AGR-326, a 3-page illustrated fact sheet by Brent Sellers, J. Ferrell, and Reyna Speckmann, describes the biology and control of this native evergreen shrub that, in dense infestations, can completely eliminate bahiagrass stands in pastures. Published by the UF Department of Agronomy, November 2009. Reviewed December 2012.